Prevalence of Toxoplasma gondii and Cytomegalovirus in Sera of Aborted Women in Zawia City - Wafaa A Al Bashier,; Mabrouka A Khalleefah,; Faten I Bshena,; Fatma Abd Twair,; Ali Y Alkhboli, (AlQalam Journal of Medical and Applied Sciences, 2024)
Toxoplasmosis is caused by the parasite Toxoplasma gondii. This disease is widespread and is considered a zoonotic disease. Infection with this disease leads to stillbirth, miscarriage, or a birth defect during pregnancy. Aim of the study is to determine the seroprevalence of Toxoplasma gondii in the city of Zawia. Over ten months Two hundred and eleven serum samples were collected from pregnant women To be examined for Toxoplasma gondii and cytomegalovirus at Al-Zawiya Hospital, Al-Zawiya city, Libya, and the Toxoplasma gondii parasite and cytomegalovirus were examined. The majority of aborted women were in the age group of 21-30 years (53.1%), followed by the 31-40 years age group (31.7%). Toxoplasmosis infection was more prevalent (32.7%) than cytomegalovirus (CMV) infection (15.2%), with a relatively low co-infection rate (6.6%). IgG (past/chronic infection) was present in 50.7% of cases, and IgM (recent/acute infection) in 59.2%. CMV: IgG was present in 35.5% of cases, and IgM in 69.7%. No significant association between toxoplasmosis IgG and CMV IgG. Significant association between toxoplasmosis IgG and CMV IgM, indicating a relationship between past/chronic toxoplasmosis and recent CMV infection. Highly significant association between toxoplasmosis IgM and CMV IgG, suggesting a link between recent toxoplasmosis and past/chronic CMV infection. Highly significant association between toxoplasmosis IgM and CMV IgM, indicating a strong relationship between recent infections of both pathogens. A serological screening program for early detection of toxoplasmosis and cytomegalovirus (CMV) infection in pregnant women and aborted women in Libya is considered essential to avoid all causes that pose problems for women. داء المقوسات يسببه طفيل التوكسوبلازما جوندي. وهذا المرض منتشر على نطاق واسع ويعتبر مرضًا حيوانيًا. تؤدي الإصابة بهذا المرض. إلى ولادة جنين ميت، أو إجهاض، أو عيب خلقي أثناء الحمل. الهدف من هذه الدراسة هو تحديد معدل الانتشار المصلي لمرض التوكسوبلازما جوندي في مدينة الزاوية، الطرق: على مدى عشرة أشهر تم جمع مائتين وأحد عشر عينة مصل من النساء الحوامل لفحصها لمرض التوكسوبلازما جوندي والفيروس المضخم للخلايا في مستشفى الزاوية، مدينة الزاوية. مدينة الزاوية، ليبيا، تم فحص طفيل التوكسوبلازما جوندي والفيروس المضخم للخلايا.النتيجة: أظهرت نتائج هذه الدراسة أن التوزيع العمري: غالبية النساء المجهضات كن في الفئة العمرية 21-30 سنة (53.1%)، تليها الفئة العمرية 31-40 سنة (31.7%). وانتشار العدوى: كانت عدوى داء المقوسات أكثر انتشارًا (32.7%) من عدوى الفيروس المضخم للخلايا (CMV) (15.2%)، مع معدل منخفض نسبيًا للعدوى المصاحبة (6.6%). وملامح الأجسام المضادة: داء المقوسات: كان IgG (عدوى سابقة/مزمنة) موجودًا في 50.7% من الحالات، وIgM (عدوى حديثة/حادة) في 59.2%. الفيروس المضخم للخلايا (CMV): كان IgG موجودًا في 35.5% من الحالات، وIgM في 69.7%. والجميع: لا يوجد ارتباط كبير بين داء المقوسات IgG وCMV IgG. وجود ارتباط كبير بين داء المقوسات IgG وCMV IgM، مما يشير إلى وجود علاقة بين داء المقوسات السابق/المزمن والعدوى الحديثة بفيروس CMV. هناك ارتباط كبير للغاية بين داء المقوسات IgM وCMV IgG، مما يشير إلى وجود صلة بين داء المقوسات الحديث وعدوى CMV السابقة/المزمنة. هناك ارتباط كبير للغاية بين داء المقوسات IgM وCMV IgM، مما يشير إلى وجود علاقة قوية بين الإصابات الحديثة لكلا الممرضين. الاستنتاج: يعتبر برنامج الفحص المصلي للكشف المبكر عن عدوى داء المقوسات والفيروس المضخم للخلايا لدى النساء الحوامل والنساء المجهضات في ليبيا ضروريا لتجنب جميع الأسباب التي تشكل مشاكل